Training on Implementation of the Merdeka Belajar Curriculum for Teachers of Perkampungan Minangkabau Boarding School - Dinovia Fannil Kher; Yati Aisya Rani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
To support one of the government's programs in the field of education, the use of the Merdeka Belajar Curriculum, it is necessary to provide outreach and training to all elements of educational practitioners, especially teachers. Pesantren Perkampungan Minangkabau was chosen as a partner based on the greatest desire of the Islamic Boarding School and the Foundation, namely, to continue to follow the current development of the education system launched by the Republic of Indonesia. From the results of internal meetings between Islamic Boarding Schools and Foundations, one necessary thing is implementing the Merdeka Belajar Curriculum in their environment. The main problem is that teachers or members of the Foundation need to understand the concept of the Merdeka Belajar Curriculum. The method used in this community service is a workshop. From the results of the pre-test conducted before the workshop, even though around 83% of participants had heard and often heard of the Merdeka Belajar Curriculum, it turned out that only 3.6% stated that they understood how to implement the Merdeka Belajar Curriculum. The rest said they did not understand enough or did not understand (41.6%), and more than half admitted they did not understand at all (54.5%). After the training, it was found that 78.2% understood the essence, procedures, and implementation of the Merdeka Belajar Curriculum.